Intimate partner violence against pregnant women: the environment according to Levine's nursing theory - Selma Villas Boas Teixeira; Maria Aparecida Vasconcelos Moura; Leila Rangel da Silva; Ana Beatriz Azevedo Queiroz; Kleyde Ventura de Souza; Leônidas Albuquerque Netto (SciELO, 2015)
Abstract OBJECTIVE Analyzing the elements that compose the environment of pregnant women who have experienced intimate partner violence in the light of Levine's Nursing Theory. METHOD A qualitative, descriptive study conducted from September to January 2012, with nine pregnant women in a Municipal Health Center in Rio de Janeiro. The interviews were semi-structured and individual. The theoretical framework was based on Levine's Nursing Theory. RESULTS Thematic analysis evidenced the elements that composed the external environment, such as violence perpetrated by intimate partners before and during pregnancy, violence in childhood and adolescence, alcohol consumption and drug use by the partner, unemployment, low education and economic dependency, which affected health and posed risks to the pregnancy. CONCLUSION Violence perpetrated by an intimate partner was the main external factor that influenced the internal environment with repercussions on health. This theory represents a tool in nursing care which will aid in detecting cases and the fight against violence.